2009
DOI: 10.1007/s11274-009-0190-4
|View full text |Cite
|
Sign up to set email alerts
|

β-Xylosidases from filamentous fungi: an overview

Abstract: b-Xylosidases are hydrolytic enzymes which play an important role in xylan degradation, hydrolyzing xylobiose and xylooligosaccharides to xylose from the nonreducing end. Filamentous fungi are particularly interesting producers of this enzyme from an industrial point of view, due to the fact that they secrete b-xylosidases into the medium. Besides, fungal b-xylosidases are highly advantageous for their elevated activity levels and specificity. Interest in xylanolytic enzymes has been increasing, for their poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(108 citation statements)
references
References 171 publications
5
84
0
19
Order By: Relevance
“…The difference between the molecular masses determined by size-exclusion chromatography and SDS-PAGE suggests that BxTW1 works as a noncovalent dimer in its native conformation. Isoelectrofocusing indicated that the pI of the protein was 7.6, a value similar to those reported for other ␤-xylosidases (20). Nevertheless, the theoretical value obtained from the BxTW1 sequence was 4.75.…”
Section: Fig 2 Estimation Of Bxtw1 Molecular Mass By Sds-page (A) Andsupporting
confidence: 84%
See 1 more Smart Citation
“…The difference between the molecular masses determined by size-exclusion chromatography and SDS-PAGE suggests that BxTW1 works as a noncovalent dimer in its native conformation. Isoelectrofocusing indicated that the pI of the protein was 7.6, a value similar to those reported for other ␤-xylosidases (20). Nevertheless, the theoretical value obtained from the BxTW1 sequence was 4.75.…”
Section: Fig 2 Estimation Of Bxtw1 Molecular Mass By Sds-page (A) Andsupporting
confidence: 84%
“…Figure 1A shows the ␤-xylosidase inducer effect of 1% Avicel, 1% D-xylose, or 1%, 2%, or 3% beechwood xylan over 6 days. A control culture with 1% Dglucose as the carbon source, which inhibits xylanase production by carbon catabolite repression (20), was also tested. The highest ␤-xylosidase activity was detected when 2% beechwood xylan was used as the inductor, and the profile of total secreted proteins was similar to that detected with 3% xylan.…”
Section: Resultsmentioning
confidence: 99%
“…1a, c). β-xylosidase plays a key role in the complete hydrolysis of XOS into xylose (Knob et al 2009). As shown in Fig.…”
Section: Analysis Of Xylan-degrading Enzymes From a Niger Be-2 And Hmentioning
confidence: 99%
“…Enzymatic hydrolysis of xylan involves the synergistic action of several main chain-and side group-cleaving enzymes, including endo-β-1,4-xylanases (EC 3.2.1.8), β-xylosidases (EC 3.2.1.37), α-arabinofuranosidases (EC 3.2.1.55), α-glucuronidases (EC 3.2.1.139), acetyl xylan esterases (EC 3.1.1.72), and feruloyl esterases (EC 3.1.1.73) (de Vries and Visser 2001). Endo-β-1,4-xylanases as the main xylan-degrading enzymes randomly cleave the internal β-1,4-glycosyl bonds in the xylan main chain producing xylooligomers (Zhang et al 2011), and β-xylosidases convert xylooligomers to xylose monomers (Knob et al 2009). Species of Trichoderma and Aspergillus are used as producers of enzymes that deconstruct lignocellulosic biomass by various companies (Banerjee et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Filamentous fungi usually secrete plant cell wall degrading enzymes into the medium, releasing energy and nutrients from plant biopolymers. This physiological characteristic is interesting from the industrial point of view because it eliminates the need for releasing the enzymes by cell disruption in the downstream process; moreover the levels of extracellular enzymes produced by fungi are higher than those from yeasts and bacteria (KNOB et al, 2010).…”
Section: Introductionmentioning
confidence: 99%